A Cross Sectional Study on Vaccination Coverage of Children in the Urban Slums of Bangalore - Manuja LM; Viswanatha PG; Veena NH; Ranganath TS (Medsci Publications, 2018)
Background: Despite their public health benefit, vaccination pro- grams face obstacles. The objectives of the study were to determine the vaccination coverage among the children in urban slums in Bangalore and to determine the factors associated with partial immunization. Methodology: This cross sectional study was carried out among 210 children aged between 12-23 months in urban slums of Banga- lore from June 2015 to May 2016 using 30-cluster survey method. Information regarding immunization status, socio demographic and personal details was collected using pretested semi structured questionnaire after obtaining the consent. Data was entered in MS EXCEL and was analyzed, using percentages and chi square test. Results: Among 210 children, Male children constituted 53.8%. Full immunization coverage was 83.3% and Partial immunization coverage was 16.7%. The relation between socio demographic var- iables like religion, type of family, total number of children in fam- ily, birth order, place of delivery, father's and mother's educational status, socioeconomic status and immunization status was found to be statistically significant. Conclusion: Illiterate father, illiterate mother, low socio economic status, no exclusive breast feeding and non availability of immun- ization card were determinants of partial immunization.